Indian Cheilanthoid fern - A numerical taxonomic approach (Bangladesh Journal of Plant Taxonomy, 2016)
Twenty one species belonging to five genera (viz. Aleuritopteris F?e, Cheilanthes Sw., Doryopteris J. Sm., Notholaena R. Brown, Pellaea Link.) of the Indian cheilanthoid ferns were studied to develop the new data set of micromorphological details viz. epidermal cells, stomatal morphotypes, venation pattern and spore ultrastructre. Cluster analysis was performed by using the two- state of multiple characters that separate the genus Aleuritopteris from Cheilanthes at the Eucladian distance of 5.1, though completely linked with other closely related genera, viz. Doryopteris, Notholaena and Pellaea. The taxonomic conundrum lies within these genera was resolved with numerical taxonomic study.Bangladesh J. Plant Taxon. 23(2): 133-142, 2016 (December)